Technological Improvements in Commercial Eucheuma Cultivation (A Short Communication) - Ask, Erik; Azanza, Rhodora; Simbik, Made; Cay-An, Recarte; Lagahid, Jose (Science Diliman: A Journal of Pure and Applied Sciences; Vol 15 No 2 (2003), 2012)
Two new devices developed by FMC BioPolymer for attaching propagules of the commercial Eucheumas Kappaphycus alvarezii and Eucheuma denticulatum to farm lines (the Eclip and Made Loop) were tested against the conventional Tie-tie system based on growth rate, percent plant loss, seeding and stripping time, as well as cost. Compared to the Tie-tie system, growth rates and percent plant loss were not statistically different with the Eclip and Made Loop. Seeding time is four times faster with the Made Loop and twice as fast with the Eclip. Stripping the line took a similar amount of time with the Eclip, but is 30 times faster with the Made Loop. The material cost of the Made Loop is similar to Tie-tie, although the Eclip is over ten times more costly. The cost of the Tie-tie did not include the fact that the Made Loop will last two years while the Tie-tie lasts no more than three months and, subsequently labor must be expended at least eight times as often to replace them on the main farm line.